Analysis of the quantities of the remanufacturing plan of perfect cost - Pedro Pi\~neyro; Omar Viera (Journal of Remanufacturing, 2012)
Background: The remanufacturing plan of perfect cost makes reference to the remanufacturing plan of an optimal solution of the economic lot-sizing problem with remanufacturing (ELSR). In this paper, we address the problem of determining the quantities of the remanufacturing plan of perfect cost in an independent way. Results: Assuming that the periods where remanufacturing is carried out are known in advance and certain other assumptions on the costs, we can show that the total remanufacturing quantity of a remanufacturing plan of perfect cost can be determined separately and in a time-effective way. Conclusions: We consider that the theoretical results obtained in this paper contribute to a deeper knowledge of the characteristics of the ELSR optimal solutions. Thus, the results obtained can be used to develop an effective algorithm for solving the ELSR.
Keywords: 650; remanufacturing; economic lot-sizing problem; inventory control; reverse logistics; Produkt-Recycling; Losgröße; Lagerhaltungsmodell; Betriebliche Kreislaufwirtschaft